نظام القبول ومشكلات التدريس في برنامج دبلوم التأهيل التربوي في الجامعة الافتراضية السورية من وجهة نظر الدارسين والتقنيين - حلاق محمد; إبراهيم هيفاء حسن (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى التعرف إلى نظام القبول ومشكلات التدريس في الجامعة الافتراضية السورية من وجهة نظر الدارسين والتقنيين في برنامج دبلوم التأهيل التربوي الذي يقام كاتفاقية بين وزارة التربية والجامعة الافتراضية السورية، وذلك بهدف تأهيلهم، وهم على رأس عملهم كمدرسين..وقد طبق البحث على عينة "عشوائية طبقية" مؤلفة من (300) دارس ودارسة في برنامج دبلوم التأهيل التربوي في الجامعة الافتراضية السورية، و(33) تقنياً من (مشرفي مراكز النفاذ، فريق الدعم التقني). تكونت أدوات البحث من استبانة موجهة للدارسين مؤلفة من (50) بنداً، وأخرى موجهة للتقنيين مكونة من (17) بنداً. واتبع الباحث المنهجَ الوصفي التحليلي في استخلاص نتائج هذا البحث، وتوصل إلى أن المشكلات الأكثر حدةً التي كان يعانيها الدارسون هي المشكلات المتعلقة بالتقنية، والمشكلات الأكثر حدةً التي يعانيها التقنيون هي المشكلات المتعلقة بعدم متابعة الدارسين بريدهم الالكتروني، وأنه لا توجد فروق ذات دلالة إحصائية بين متوسطات تقديرات الدارسين تبعا لمتغير الجنس والعمر، ولا توجد فروق ذات دلالة إحصائية بين متوسطات فريقي التقنيين (الدعم التقني، وفريق مراكز النفاذ)، تبعاً لمتغير الخبرة عند مستوى الدلالة (0,05). The purpose of this research was to become acquainted with the virtual learning problems at the Syrian Virtual University from the viewpoint of lecturers, students and executive staff. The research is conducted within the scope of the educational diploma qualification program, which is carried out as a contract between the Ministry of Education and the Syrian Virtual University to qualify them as teachers while at work. This research implemented on “stratified, random” sample of (300) students in educational diploma program at the Syrian Virtual University, and (33) technicians (supervisors of access centres and technical support team). The research tools included a questionnaire containing (50) questions for the students, and another one for technicians containing (17) questions. The researcher followed the descriptive analytic method in obtaining the results of this study. The researcher found that the most important problems that students suffer from were those related to technology, while and the technicians are suffering from the fact that students do not check their e-mails. Moreover, there are no statistically significant differences between averages of students according to the age and gender variable, and there are no statistically significant differences between the averages of the two technical teams (technical support, and access centres team) according to the experience variable on the pointed level (0.05).